Evaluation of a Combined HIV and Geriatrics Clinic for Older People Living with HIV: The Silver Clinic in Brighton, UK - Tom Levett; Katie Alford; Jonathan Roberts; Zoe Adler; Juliet Wright; Jaime H. Vera (Geriatrics, 2020)
As life expectancy in people living with HIV (PLWH) has increased, the focus of management has shifted to preventing and treating chronic illnesses, but few services exist for the assessment and management of these individuals. Here, we provide an initial description of a geriatric service for people living with HIV and present data from a service evaluation undertaken in the clinic. We conducted an evaluation of the first 52 patients seen in the clinic between 2016 and 2019. We present patient demographic data, assessment outcomes, diagnoses given, and interventions delivered to those seen in the clinic. The average age of attendees was 67. Primary reasons for referral to the clinic included management of complex comorbidities, polypharmacy, and suspected geriatric syndrome (falls, frailty, poor mobility, or cognitive decline). The median (range) number of comorbidities and comedications (non-antiretrovirals) was 7 (2–19) and 9 (1–15), respectively. All attendees had an undetectable viral load. Geriatric syndromes were observed in 26 (50%) patients reviewed in the clinic, with frailty and mental health disease being the most common syndromes. Interventions offered to patients included combination antiretroviral therapy modification, further health investigations, signposting to rehabilitation or social care services, and in-clinic advice. High levels of acceptability among patients and healthcare professionals were reported. The evaluation suggests that specialist geriatric HIV services might play a role in the management of older people with HIV with geriatric syndromes.